Premorbid Use of Statin and Outcome of Acute Ischemic Stroke After Intravenous Thrombolysis: A Meta-Analysis - Liu, Jia; Wang, Qinghai; Ye, Chaoqun; Li, Gaifen; Zhang, Bowei; Ji, Zhili; Ji, Xunming (Frontiers in Neurology, 2020)
Background: Association between premorbid use of statin and early outcomes of acute ischemic stroke (AIS) after intravenous thrombolysis (IVT) remains uncertain. We performed a meta-analysis of observational studies to evaluate the influence of premorbid use of statin on functional outcome and symptomatic intracranial hemorrhage (SIH) in AIS after IVT. Methods: Relevant studies were identified by search of PubMed, Embase, and Cochrane’s Library databases. Only studies with multivariate analyses were included. A random-effect model, incorporating the inter-study heterogeneity, was used to pool the results. Results: Twenty observational studies with 20,752 AIS patients who were treated with IVT were included. Pooled results showed that premorbid use of statin was not associated with improved 3-month favorable functional outcome (odds ratio [OR]: 1.05, 95% confidence interval [CI]: 0.87-1.26, p=0.60, I2=52%), 3-month functional independence (OR: 1.13, 95% CI: 0.96-1.33, p=0.15, I2=52%), or 3-month mortality (OR: 1.12, 95% CI: 0.94-1.34, p=0.20, I2=20%). Moreover, premorbid use of statin was associated with an increased risk of SIH in AIS after IVT (OR: 1.48, 95% CI: 1.12-1.95, p=0.006, I2=60%). Subgroup analyses according to study design, adjustment of baseline low-density lipoprotein cholesterol, and definitions of SIH showed consistent results (p values for subgroup difference all > 0.05). Conclusions: Premorbid use of statin is not associated with improved functional outcomes or mortality, but is associated with a higher risk of SIH in AIS patients after IVT.